Efektifitas CSR Dalam Meningkatkan Citra Perusahaan PT.ASN - Dira Ranisa; Hanifah Nurdin (SADIDA, 2022)
Agro Sinergi Nusantara which is engaged in oil palm plantations, since its establishment in 2011 until now has never been demonstrated or received rejection from the community. The company always implements CSR or social responsibility programs. The purpose of this research is to seek and find knowledge that can be used directly in life. In conducting this study, the author uses a qualitative analysis approach and descriptive method. The findings that the authors get are; focus of CSR implementation of PT. Agro Sinergi Nusantara Kebun Ujung Lamie in 5 fields, education, environment, infrastructure, social and health. CSR PT. Agro Sinergi Nusantara can be classified into a centralized circle model, because CSR in the company focuses on its responsibilities on the economic aspect, but also does not forget its responsibilities to other aspects and are interrelated with each other. This can be seen from the formation and increasing image of the company. Keywords: Company image, Corporate Social Responsibility (CSR)